Rate of Anorectal Sexually Transmitted Diseases in Male Patients who Practice Receptive Anogenital Sexual Intercourse - เจริญวัฒนาโชคชัย, อังคณา; เย็นยาซัน, นฤมล; อยู่ประเสริฐ, รัชฎา (Disease Control Journal, 2009)
The purpose of this descriptive study was to study the rate of anorectal sexually transmitted diseases in male patients who practice receptive anogenital sexual intercourse and the interrelationship of infections between anorectum and urethra in men practicing receptive anal sexual intercourse who attended Clinical Research Section (Bangrak Hospital), Sexually Transmitted Infections Cluster. From December 1st 2004 to February 28th 2005, 77 men who practiced receptive anal sexual intercourse were enrolled. The symptoms and signs were evaluated .The specimens from urethra and rectum were taken for gram stain, culture for Neisseria gonorrhoeae and ELISA (enzyme linked immunosorbent assay) test for Chlamydia trachomatis. The ulcer (if presented) were taken for detection of Treponema pallidum, Haemophilus ducreyi and Herpes simplex virus. The prevalence of anorectal sexually transmitted diseases was found in 13 cases (16.88%). Rectal chlamydia was detected in 7 cases (9.1%) and rectal gonorrhea was detected in 1 case (1.3%). Anal warts was detected in 5 cases (6.4%).Those with rectal chlamydia and gonorrhea were asymptomatic. Using the routine Gram' stain from specimen could not detect and diagnose both chlamydia and gonorrhea. Two cases of anal warts presented with anal lumps and two could identify that they had anal warts. One case of anal wart was asymptomatic. Correlating gonococcal and chlamydial infections in rectum with urethra , 6 patients (75%)with rectal gonorrhea or chlamydia had no disease in the urethra. In conclusion, the rate of anorectal sexually transmitted diseases in male patients who practice receptive anogenital sexual intercourse was not uncommon. Patients with anal warts mostly recognised the condition and seeked tratment. Rectal chlamydia and gonorrhea were mostly asymptomatic and , to diagnose these infections, special laboratory tests were recommended.